DESAIN DAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS MICROSOFT EXCELL DI SEKOLAH KRISTEN PELITA NUSANTARA KASIH SURAKARTA - Trian Yosikawati, Gloria Paska; Jea Manurung, Felicia Feivel; Dewanti, Septa Kurnia; Nany, Magdalena; Cahjono, Mardanung Patmo; Mujiyono, Mujiyono (Jurnal Pengabdian Bukit Pengharapan, 2024)
The growth in the number of students and administrative needs at Pelita Nusantara Kasih Christian School (SKPNK) is getting more and more complex day by day. Prior to this system, SKPNK faced various serious challenges in financial management. Problems such as difficulties in separating data per school unit, complexity in recording transactions, and the absence of an automatic book-closing feature greatly affect the quality of reporting and management decision-making. To deal with these problems, the development team created a comprehensive accounting system that took into account several important criteria, such as ease of use, low cost, and acceptance by school staff. The system development process is carried out systematically, starting from problem identification, in-depth data collection, proposal preparation, to system design and testing. The results are very satisfactory, this system not only simplifies financial management, but also improves data accuracy and speeds up the reporting process. The implementation of an Excel-based accounting system at SKPNK has proven that simple technology solutions can have a significant impact on the financial management of an educational institution